2020
DOI: 10.1016/j.watres.2020.115835
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability and key influencing factors of river fecal coliform within a typical complex watershed

Abstract: a b s t r a c tFecal coliform bacteria are a key indicator of human health risks; however, the spatiotemporal variability and key influencing factors of river fecal coliform have yet to be explored in a rural-suburban-urban watershed with multiple land uses. In this study, the fecal coliform concentrations in 21 river sections were monitored for 20 months, and 441 samples were analyzed. Multivariable regressions were used to evaluate the spatiotemporal dynamics of fecal coliform. The results showed that spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 60 publications
1
23
0
1
Order By: Relevance
“…Tryptophan-like component C3 (280/290 ~ 350nm) was a kind of biodegradable protein-like substance, associating with the aromatic ring structure of amino acids in DOM. Fluorescence peaks of C3 (280/290 ~ 350nm) appeared in a region with a shorter wavelength of emission (λ Em < 380nm) (Zhang et al, 2020). The component was closely related to the organic matter in sewage, which was regarded as anthropogenic or produced from plankton action over anthropogenic organics (Meng et al, 2013).…”
Section: Components and Spectral Characteristics Of Dommentioning
confidence: 99%
See 3 more Smart Citations
“…Tryptophan-like component C3 (280/290 ~ 350nm) was a kind of biodegradable protein-like substance, associating with the aromatic ring structure of amino acids in DOM. Fluorescence peaks of C3 (280/290 ~ 350nm) appeared in a region with a shorter wavelength of emission (λ Em < 380nm) (Zhang et al, 2020). The component was closely related to the organic matter in sewage, which was regarded as anthropogenic or produced from plankton action over anthropogenic organics (Meng et al, 2013).…”
Section: Components and Spectral Characteristics Of Dommentioning
confidence: 99%
“…What's more, the ultraviolet fulvic acid-like component (235-250/385-430nm) contained a large number of phenolic hydroxyl carbonyl groups and other functional groups. And these humic-like uorescence peaks both have connections with its hydroxyl and carboxyl groups in the structure (Zhang et al, 2020). Humic-like C1 (230, 335/400nm) and C2 (260, 360/450nm) usually indicated terrestrial humus and anthropogenic activities that came from forest streams (Derrien et al, 2018), agricultural basins (Williams et al, 2013), stormwater (Graeber et al, 2012), sewage (Fuss et al, 2017).…”
Section: Components and Spectral Characteristics Of Dommentioning
confidence: 99%
See 2 more Smart Citations
“…Also, large amounts of pollutants are transported to drainage systems and downstream water bodies during rainfall events, causing severe runoff pollution [1]. Some research has shown that this pollution can lead to serious deterioration of urban water quality and greatly affect the health of both human beings and aquatic organisms [2]. It is of great importance to systematically analyse the characteristics of runoff pollution in some typical highly urbanized regions considering landscape patterns and rainfall events.…”
Section: Introductionmentioning
confidence: 99%